Endodontic treatment of pulpal and periodontal diseases (Part 2). Application of calcium hydroxide in endodontic treatment (LLC "Endo Press", 2020)
The article represents the review of the russian and foreign literature devoted to various mechanisms of antibacterial activity of calcium hydroxide. Methods of entering and removal of a preparation from the root canals are surveyed. The attention is paid to influence of a vehicle on antibacterial activity of calcium hydroxide. Effectiveness of conservative treatment depends on the form of periodontitis, used tools and techniques, body resistance, the presence of somatic diseases. Currently, much attention is paid to the calcium hydroxide preparations on the basis of a viscous, which include the iodoform.